Shining pythagoreans - Godenzi Alegre, Jorge Luis (2021)
According to the Pythagoreans, life is a punishment and duty to live it is a mandate, it was inescapable role of philosophy as speculative conception, to teach how to live. The best way of life, the happiest was the vita beata. That theoretical life meant an ascetic lifestyle. Its essence lay in contemplation. As styles or lower forms of life, were, according to the Pythagorean philosophy, practical life corresponding to the statesmen and rulers; apoláustica life and that was particular to the merchants and businessmen. According to the Pythagorean conception of philosophy in its fundamentals was contemplative. The philosopher, therefore, was a spectator, a spectator par excellence. But what should be foremost contemplation as the Pythagorean doctrine? The Pythagoreans responded that the object of philosophical contemplation should be the sky. The Pythagoreans were the ones who, for the first time, gave the name of the orderly cosmos of the universe together. Since then, the word "cosmos" became a fundamental category of any system of philosophy. The sky is, according to the Pythagoreans, the best place to order and harmony of the universe is reflected. The universe is order and harmony and the soul must be too.